Cardiovascular outcomes of sodium-glucose cotransporter 2 inhibitors: A comprehensive review of clinical and preclinical studies. (1st June 2016) - Ghosh, Raktim Kumar; Bandyopadhyay, Dhrubajyoti; Hajra, Adrija; Biswas, Monodeep; Gupta, Anjan
Abstract: Diabetes is a leading cause of morbidity and mortality worldwide. Management of diabetes is changing at a rapid pace. Three new classes of antidiabetic drugs including GLP-1 (Glucagon-like peptide 1), DPP-IV (Dipeptidyl peptidase IV) and SGLT2 (Sodium glucose cotransporter 2) inhibitors have been approved in the last few years. Treating diabetes with the antidiabetic drug does not always reduce the cardiovascular complications of diabetes. On the contrary, there was a huge controversy regarding the effect of rosiglitazone on cardiovascular risk reduction a few years ago. Since then, submission of postmarketing cardiovascular outcome study data has been mandated by US FDA and other drug regulatory agencies for newer antidiabetic medications. This is to avoid further premature claims regarding cardiovascular harm or safety of the newer classes. We already have some cardiovascular safety data available on DPP-IV and GLP-1 groups of medications. Dapagliflozin, canagliflozin, and empagliflozin are currently approved SGLT2 inhibitors. We do not have sufficient cardiovascular outcome data available for this novel class. However, this group of drugs, which act by increasing renal glucose excretion, have also shown some non-glycemic benefits including weight reduction, blood pressure control, diuretic action, renal protection, decrease in arterial stiffness and uric acid reduction. Empagliflozin, a new member of SGLT2 class, showed significant cardiovascular morbidity and mortality benefit in recently published EMPA-REG OUTCOME trial. The authors summarize all the published clinical and preclinical cardiovascular outcome data of SGLT2 inhibitors, including recently completed and ongoing major clinical trials in this comprehensive review. Highlights: Dapagliflozin, canagliflozin, and empagliflozin currently approved SGLT2 inhibitors Reduce blood pressure, arterial stiffness, body weight, visceral adiposity Reduce albuminuria, serum uric acid level and oxidative stress Empagliflozin showed CV morbidity and mortality benefit. EMPA-REG Outcome, CANVAS, CREDENCE and DECLARE-TIMI 58 major trials